Towards a Model of User Experience in Immersive Virtual Environments - Loup, Guillaume; Loup-Escande, Emilie; Christmann, Olivier; Tcha-Tokey, Katy; Richir, Simon (Advances in human-computer interaction, 2018)
There are increasing new advances in virtual reality technologies as well as a rise in learning virtual environments for which several studies highlighted the pedagogical value, knowledge transfer, and learners’ engaged-behaviors. Moreover, the notion of user experience is now abundant in the scientific literature without the fact that there are specific models for immersive environments. This paper aims at proposing and validating a model of User eXperience in Immersive Virtual Environment, including virtual learning environments. The model is composed of 10 components extracted from existing models (i.e., presence, engagement, immersion, flow, usability, skill, emotion, experience consequence, judgement, and technology adoption). It was validated in a user study involving 152 participants who were asked to use the edutainment application Think and Shoot and to complete an immersive virtual environment questionnaire. The findings lead us to a modified user experience model questioning new paths between user experience components (e.g., the influence of experience consequence on flow).